Screen to Intervene; establishing a dedicated metabolic clinic for patients with chronic mental illness in an Irish Metal Health Service. (1st June 2022) - Usman, M.; Saleem, F.; Mccafferty, B.; Tan, J.H.P.; Zubir, M.; Adamis, D.
Abstract : Introduction: People with serious mental illness exhibit higher morbidity and mortality rates of chronic diseases than the general population. Objectives: The aim of this study was to establish a dedicated clinic for patients with chronic mental illness to monitor physical health in accordance with best practice guidelines. Methods: Patients were invited to attend the metabolic clinic. The following areas were examined: Personal and family history of cardiovascular disease, diet, exercise, smoking. Mental state examination, waist circumference, BP, pulse, ECG and BMI. Laboratory tests including U+E, LFTs, HbA1c, Lipid profile and other tests as appropriate such as serum lithium. AIMS scale, HoNOS and WHOQOL-BREF scales as additional indicators of global health. Results: A total of 80 patients attended during 3.5 years of clinic. Mean age was 54.9 years (SD:13.81) at first contact and 45% were females. Mean years in the service was 19.66 (SD:11.54) and mean number of previous hospital admissions was 4.4 (SD:5.63). Metabolic syndrome was present in 42% at first assessment and 20% had at least one new physical abnormality identified during the clinic. A statistically significant difference was found for the psychological domain of the WHOQOL-BREF and the HoNOs particularly at third assessment. ( β =4.64, Wald x 2 =7.38, df:1, p=0.007, CI:1.3-8.1, β =-.889, Wald x 2 =4.08, df:1, p=0.043, CI: -1.752 to-.026) respectively. Conclusions: The results show a high prevalence of physical health conditions in this cohort, some of which represent a new diagnosis. This implicates better allocation of existing resources for screening and early detection, and potential to run joint clinics with primary care. Disclosure: No significant relationships.